Enhancing Online Instructional Approaches for Sustainable Business Education in the Current and Post-Pandemic Era: An Action Research Study of Student Engagement - Lui-Kwan Ng; Chung-Kwan Lo (MDPI AG, 2022)
The outbreak of the COVID-19 pandemic has pushed traditional classroom instruction to fully online teaching and learning modes. Higher education institutions in China were among the first to shift to these new modalities. The innovative integration of techno-pedagogies with the advancement of information communication technologies and multimedia applications made these rapid changes feasible in practice. However, the shift from traditional to fully online instruction was challenging. Student disengagement and learning performance losses due to these pedagogical changes have impacted the sustainability of educational programmes. We used mixed methods with dual-cycle action research to explore better pedagogical solutions. Seventy-six adult students, three teachers and three teaching assistants were involved in our study. Informed by the results of the first action research cycle, gamification was introduced in the second cycle. The gamified flipped classroom approach in the second action research cycle significantly improved student engagement, and their learning performance was sustained throughout the study. Suggestions for flexibility, all-in-inclusive, coopetitive learning, technical support and sustainable learning (F.A.C.T.S.) are proposed as a practical framework for new techno-pedagogical approaches in the current and post-COVID-19 era.